(untitled) (Al-Aasar, 2025)
The legal maxim Al-Umur bi Maqasidiha (Matters are judged by their objectives) is regarded as one of the most fundamental principles in Islamic jurisprudence. It serves as a guiding framework in determining the validity, legality, and moral value of actions based on the underlying intention behind them. This paper provides a research-oriented and applied study of the maxim, exploring its theoretical foundations in the Qur’an and Sunnah, its development within classical and contemporary Fiqh literature and its applications in various fields of Islamic law such as worship, transactions, family law, and criminal justice. The study also examines the maxim’s relevance in contemporary socio-legal contexts, highlighting its role in aligning legal rulings with ethical considerations and higher objectives of Shri‘ah. By offering both a conceptual and practical analysis, this paper demonstrates the enduring importance of Al-Umur bi Maqasidiha in understanding and applying Islamic legal principles.